Case report: Improvement of gait with adaptive deep brain stimulation in a patient with Parkinson’s disease - Isaias, Ioannis U.; Caffi, Laura; Borellini, Linda; Ampollini, Antonella M.; Locatelli, Marco; Pezzoli, Gianni; Mazzoni, Alberto; Palmisano, Chiara (Frontiers in Bioengineering and Biotechnology, 2024)
Gait disturbance is a common and severe symptom of Parkinson’s disease that severely impairs quality of life. Current treatments provide only partial benefits with wide variability in outcomes. Also, deep brain stimulation of the subthalamic nucleus (STN-DBS), a mainstay treatment for bradykinetic-rigid symptoms and parkinsonian tremor, is poorly effective on gait. We applied a novel DBS paradigm, adjusting the current amplitude linearly with respect to subthalamic beta power (adaptive DBS), in one parkinsonian patient with gait impairment and chronically stimulated with conventional DBS. We studied the kinematics of gait and gait initiation (anticipatory postural adjustments) as well as subthalamic beta oscillations with both conventional and adaptive DBS. With adaptive DBS, the patient showed a consistent and long-lasting improvement in walking while retaining benefits on other disease-related symptoms. We suggest that adaptive DBS can benefit gait in Parkinson’s disease possibly by avoiding overstimulation and dysfunctional entrainment of the supraspinal locomotor network.